ANALISIS PENERAPAN AKUNTANSI SUMBER DAYA MANUSIA DAN PENGARUHNYA TERHADAP KINERJA LAPORAN KEUANGAN - Erdha Ayu Caesarani; Negina Kencono Putri; Hijroh Rokhayati (Jurnal Bisnis dan Ekonomi, 2014)
The research aimed to investigate financial statement when implementing human resource accounting and obtain empiricalresults about the financial performance before and after the implementation of human resource accounting. The researchused descriptive quantitative research method. The data that used in this research is a secondary data, including financialdata about human resources, balance sheet, and income statement of PD BPR BKK Purwokerto for 2011, 2012, and 2013.Data were obtained by way of documentation, interviews, and direct observation. Based on the result of research andanalysis of the data by using the paired sample t-test showed that there were no differences in the financial statementbefore and after applying human resource accounting, but there are differences in the financial performance before andafter the implementation of human resource accounting that showed by financial ratio.Keywords : Human Resource Accounting, Financial Statements, and Financial Performance